HASIL BELAJAR PESERTA DIKLAT TEKNIS SUBSTANTIF MEDIA PEMBELAJARAN BERBASIS MULTIMEDIA (STUDI DI KANTOR KEMENTERIAN AGAMA KOTA BEKASI) - Urip Muryanto (Tatar Pasundan : Jurnal Diklat Keagamaan, 2019)
This study aims to find out the training participants 'initial knowledge about Googlebased application programs and training participants' learning outcomes after following the learning process in the Substantive Technical Training on Multimedia-based Learning held at the Bekasi City Ministry of Religion. The research method used was descriptive, where the data collection techniques in this study used technical tests, namely by pre and post test to determine aspects of participant knowledge and product assessment sheets in the form of rating scale, to assess how far the training participants' ability to operate and make products based on Google based application. The results of this study indicate that the initial knowledge of training participants is on the criteria of "less", the percentage of 13.48%, after participating in the learning process the learning outcomes in the aspects of knowledge are in the criteria of "good", percentage of 81.67% an average score of 3.07 with the criteria of "good". Keywords: Google-based Multimedia; Learning Outcomes; Training